1989
DOI: 10.3109/02841868909111177
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life During Chemotherapy in Non-Small Cell Lung Cancer Patients

Abstract: To evaluate the usefulness of chemotherapy in non-small cell lung cancer, objective response, length of remission and survival have been considered the main yardsticks. Subjective improvement and gain in Karnofsky performance status have attracted very little attention. Thirty-one patients with stages III and IV underwent combination chemotherapy with high-dose cisplatin, and were assessed with categorical scales and 100 mm visual analogue scales used by patients themselves to report on several symptoms of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

1990
1990
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(18 citation statements)
references
References 14 publications
0
17
0
1
Order By: Relevance
“…The impact of cancer on emotional well-being showed that the diagnosis and treatment can be accompanied by anxiety and depression. (24,25) Curiously, in the logistic regression analysis of our study, the scores of patients in the more advanced stages of lung cancer in the emotional well-being domain were slightly higher than those of other patients, possibly indicating better acceptance of the diagnosis of cancer or the comforting effect of the adjuvant care offered to patients in the more advanced stages of the disease.…”
Section: Resultsmentioning
confidence: 58%
“…The impact of cancer on emotional well-being showed that the diagnosis and treatment can be accompanied by anxiety and depression. (24,25) Curiously, in the logistic regression analysis of our study, the scores of patients in the more advanced stages of lung cancer in the emotional well-being domain were slightly higher than those of other patients, possibly indicating better acceptance of the diagnosis of cancer or the comforting effect of the adjuvant care offered to patients in the more advanced stages of the disease.…”
Section: Resultsmentioning
confidence: 58%
“…During recent years, quality of life (QL) has increasingly become the focus of interest in clinical cancer trials [3,5,11,14,16,19,20,22,24,31]. The methodology of QL evaluation is, however, an ongoing issue of debate [1, 10,28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, now it has been proved in various studies despite improvement in survival chemotherapy also have impact over quality of life; it reduces the symptoms like cough, hemoptyis, pain and dysponea in approximately 70% of patients and improvement in performance status and weight gain 15,16,17,18 .…”
Section: Methodsmentioning
confidence: 99%